2010
DOI: 10.1111/j.1476-4431.2010.00521.x
|View full text |Cite
|
Sign up to set email alerts
|

Controversies related to red blood cell transfusion in critically ill patients

Abstract: RBC transfusion is unequivocally indicated for treatment of anemic hypoxia. However, critical hemoglobin or Hct below which all critically ill patients require transfusion has not been established and there are inherent risks associated with allogenic blood transfusion. Clinical trials designed to evaluate the effects of RBC age and leukoreduction on veterinary patient outcome are warranted. Implementation of evidence-based transfusion guidelines and consideration of alternatives to allogenic blood transfusion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
59
0
3

Year Published

2013
2013
2016
2016

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(62 citation statements)
references
References 93 publications
0
59
0
3
Order By: Relevance
“…The immunosuppressive consequences of RBC transfusion have been recognized in human clinical medicine for many decades, and descriptions of this phenomenon have been published in both human and veterinary literature. 22,23 While transfusion-associated immune modulation has not been related to a prolonged survival of transfused RBCs, this could explain the reduced clearance of transfused RBC in some cats in this study, particularly those receiving multiple transfusions in the CM+ group. Further investigation into this phenomenon is warranted.…”
Section: Discussionmentioning
confidence: 93%
“…The immunosuppressive consequences of RBC transfusion have been recognized in human clinical medicine for many decades, and descriptions of this phenomenon have been published in both human and veterinary literature. 22,23 While transfusion-associated immune modulation has not been related to a prolonged survival of transfused RBCs, this could explain the reduced clearance of transfused RBC in some cats in this study, particularly those receiving multiple transfusions in the CM+ group. Further investigation into this phenomenon is warranted.…”
Section: Discussionmentioning
confidence: 93%
“…Likewise, multivariate analysis revealed that the dose (mL/kg) of other blood products transfused was a risk factor for transfusion-associated complications. Although transfusion-related ALI has been reviewed in the veterinary literature 33 and massive transfusion is considered a risk factor for ALI, 26 there are no published case reports of transfusion-related ALI in veterinary patients, to our knowledge. 28 Most of the recent human literature investigating transfusion-associated complications is focused on the incidence and pathogenesis of ALI, specifically transfusion-related ALI that occurs within 6 hours after a transfusion.…”
Section: Discussionmentioning
confidence: 99%
“…As mais comuns são a reação não hemolítica febril ou hipertermia, a reação alérgica, a contaminação bacteriana e a lesão pulmonar aguda (TRALI), conforme revisado por Pincelli et al (2010). A TRALI é caracterizada por um edema pulmonar agudo não cardiogênico que pode ocorrer após a transfusão de hemácia, levando a uma grave dispneia e hipoxemia e eventualmente pode ocorrer febre, hipotensão e cianose (PRITTIE, 2010). É a principal causa de mortalidade em seres humanos relacionada à transfusão (TOCCI, 2010), em animais, a TRALI foi relatada apenas em modelos experimentais (PRITTIE, 2010).…”
Section: Transfusão Sanguíneaunclassified
“…Existe atualmente um debate sobre os principais critérios para a indicação de uma transfusão sanguínea tanto em humanos como em animais, uma vez que, dependendo da causa da anemia e da quantidade e rapidez do sangue perdido, a anemia pode ser bem tolerada (PRITTIE, 2010).…”
Section: Transfusão Sanguíneaunclassified
See 1 more Smart Citation